A Rare Aldosterone-Producing Adenoma Detected by 68Ga-pentixafor PET-CT: A Case Report and Literature Review - Cui, Yunying; Zhang, Yushi; Ding, Jie; Wang, Huiping; Ma, Xiaoshen; Wang, Ou; Chang, Xiaoyan; Sun, Hao; Huo, Li; Tong, Anli (Frontiers in Endocrinology, 2019)
Context: Primary aldosteronism represents an important and common cause of hypertension and is characterized by autonomous aldosterone secretion that results in severe hypertension and hypokalemia. Nonetheless, its manifestations are atypical in some cases, which renders its diagnosis difficult. Case Description: Presented in this report is a Chinese female patient with blood pressure in the high-normal range, and her parathyroid hormone was significantly elevated. Elevated plasma aldosterone concentration plus suppressed plasma rennin activity was suggestive of primary aldosteronism. 68Ga-pentixafor positron emission tomography/computed tomography revealed an aldosterone-producing adenoma, which was globally the second of its kind ever reported so far. Moreover, the tumor was located in an extremely rare area. Conclusions: Patients with primary aldosteronism may present with normal or high-normal blood pressure and a significantly elevated parathyroid hormone. 68Ga-pentixafor PET/CT is potentially a helpful tool for the noninvasive characterization of patients with primary aldosteronism.